Usulan Perancangan Mesin Alcon Pada Dinas Kehutanan Jakarta Selatan Dengan Metode Reba - Murwan Widyantoro; Yuri Delano Regent Montororing; Herri Darsan (universitas teuku umar, 2020)
This study aims to calculate the risk value for complaints experienced by workers at the Jakarta City Park Service when moving the Alcon machine by calculating the REBA value and getting the results of A score A score is 10, a B score is 8 then the C score is 9 with a Mean Risk Level. Height and immediately required speciication action for designing erginomic aids, namely TSB (Height of Elbow Standing and JT (Hand Reach) with the TSB dimension results from the percentile results, namely 104.65 cm used as a height measurement of the Alcon Machine push table and the results of the JT dimensions from the percentile results namely 85.01 cm which is used to measure the width of the Alcon Machine push table.Keywords - Work Posture, REBA, Anthropometry, Facility Design